(untitled) (Revista Română de Jurnalism și Comunicare, 2025)
In the Republic of Moldova, journalists work across multiple platforms, from traditional television and radio to online broadcasts on websites and social media, but they rarely achieve full convergence. This study, part of the Worlds of Journalism Study (2021-2025), surveyed 305 journalists in the Republic of Moldova to examine the impact of economic constraints, donor dependence and infrastructure deficits on their multi-platform practices. The results show that 43.6% “never” or “rarely” create content for print, while over 70% publish material regularly on websites. In addition, 57.7% “never” create podcasts and only 6.6% work “always” on news apps. Although the vast majority (96.4%) have a preliminary understanding of the purpose of the platforms, real synergy between them has not yet been achieved: many publications recycle content instead of creating personalized content. However, selective adoption continues, with most journalists being proficient in text, photography and video. This “partial convergence” is driven by budgetary constraints, established editorial traditions and the desire to reach diverse audiences. Data analytics is used sporadically, and automated journalism is in its infancy. Overall, the case of the Republic of Moldova demonstrates a gradual convergence driven by resource constraints and the existence of hybrid journalism, in which individual journalists combine multiple roles. The results suggest that while electronic formats enhance audience participation, structural and economic constraints continue to limit the level of convergent innovation in transitional media contexts.